Предмет: Математика,
автор: Bezverkhova041
Помогите ПОЖАЛУЙСТА срочно очень!!!
5x^3•(-3y^2)-2x^2y•8x+6x^2y^2•3x
Ответы
Автор ответа:
0
5x^3 * (-3y^2) - (2x^2 * y * 8x) + 6x^2 * y^2 * 3x =
= -15*x^3*y^2 - 16*x^3*y + 18*x^3*y^2 =
= 3*x^3*y^2 - 16*x^3*y
(Перепроверьте, правильно ли написали пример)
= -15*x^3*y^2 - 16*x^3*y + 18*x^3*y^2 =
= 3*x^3*y^2 - 16*x^3*y
(Перепроверьте, правильно ли написали пример)
Похожие вопросы
Предмет: Английский язык,
автор: marinarazieva52
Предмет: Математика,
автор: DashaRosette
Предмет: Геометрия,
автор: an18147
Предмет: Алгебра,
автор: ENZHE62
Предмет: Математика,
автор: Ланна111